Preparation method of MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst

By compounding the layered silicate disk with cobalt sulfide or nickel nanosheets, an MS (M=Co and/or Ni)/layered silicate nanocomposite catalyst was prepared, which solved the poor permeability and low active positions of the electrolyte. The problem of this achieves efficient and long-life electrocatalytic decomposition of aquatic hydrogen.

CN116273062BActive Publication Date: 2025-02-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202111521908.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-02-18
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The existing electrolytic water hydrogen production catalysts have problems such as poor permeability, small specific surface area, easy collapse of microstructure, and few active areas, which limit the efficiency and stability of its electrocatalytic decomposition of aquatic hydrogen.

Method used

Using nano-sized layered silicate disks with cobalt sulfide or nickel nanosheets to prepare MS (M=Co and/or Ni)/layered silicate nanocomposite catalysts to form core-shell structures, which improves the catalyst hydrophilicity and structural stability of electrode materials.

Benefits of technology

The electrocatalytic decomposition of aquatic hydrogen is achieved with high efficiency and long life, which improves the specific surface area of ​​the catalyst and the exposure of active sites, and enhances the reactivity and stability of the electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003407995040000081
    Figure BDA0003407995040000081
  • Figure HDA0003407995050000011
    Figure HDA0003407995050000011
  • Figure HDA0003407995050000012
    Figure HDA0003407995050000012
Patent Text Reader

Abstract

The invention discloses a method for preparing a MS (M=Co and / or Ni) / layered silicate nanocomposite catalyst. The MS (M=Co and / or Ni) / layered silicate nanocomposite catalyst comprises MS (M=Co and / or Ni) and a single layered silicate disc, and the single layered silicate disc is used as the core in structure. The MS (M=Co and / or Ni) / layered silicate nanocomposite catalyst obtained by the invention can be used for electrocatalytic decomposition of water to produce hydrogen. The invention solves the problems that the electrolyte solution is difficult to penetrate into the electrode material in the electrocatalytic decomposition of water to produce hydrogen, the effective specific surface area of ​​the catalyst is small, and the catalytic material has low activity and poor stability, and achieves high efficiency, long life and high economic electrocatalytic hydrogen evolution performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a MS (M=Co and / or Ni) / layered silicate nano composite catalyst, belonging to the technical field of nano catalyst preparation. Background Art

[0002] At present, 80% of the world's consumable energy comes from fossil fuels such as coal, oil, and natural gas. However, the excessive consumption of fossil fuels and the continuous emission of industrial (or automobile) exhaust have caused the CO2 content in the air to reach the highest level in history, that is, the carbon peak. This situation has forced researchers to shift their attention to safe, environmentally friendly, and sustainable clean energy. Hydrogen, as a high-density energy carrier, has the advantages of green and pollution-free combustion products, and is expected to become a replacement energy for fossil fuels. Photolysis and electrolysis of water to produce hydrogen are currently recognized as the most promising hydrogen production technologies because they can utilize abundant water resources and provide high-purity hydrogen and oxygen without producing other products. However, compared with photolysis of water, electrolysis of water to produce hydrogen has attracted more attention from scientific researchers because of its simple process flow, convenient operation, and higher flexibility and applicability.

[0003] At present, the most commonly used and most efficient catalysts for hydrogen production by water electrolysis are Pt, Ir and Ru-based precious metal catalysts. However, the high price of precious metals limits their widespread application in practice. Therefore, finding non-precious metal catalysts with abundant reserves, low cost, high stability and high activity is the key to effectively improve hydrogen production by water electrolysis and promote the industrialization of water electrolysis in the future. In recent years, metal sulfides, especially nickel sulfide and cobalt sulfide, have been favored by researchers due to their good conductivity and cycle performance, abundant resources and environmental friendliness, showing broad application prospects in the fields of electrocatalytic hydrogen production, energy conversion and storage. Carbon-based materials such as carbon nanotubes, graphene, redox graphene, carbon nanofibers and carbon materials have unique structures, high specific surface areas, good mechanical properties and conductive properties, and have great application potential in the fields of electrocatalysts and supercapacitors. CN 110165171 A, CN 106298269 A, CN 110931782 B, CN 105206816 A, CN108390044 B, CN 110070996 A, CN 109873127 A, and CN 109872881 A disclose cobalt disulfide / rGO composites, cobalt nickel sulfide / nitrogen-doped carbon nanofiber composites, hollow sphere cobalt sulfide / graphene composites, nickel sulfide / graphene nanocomposites, nickel disulfide / carbon composites, nickel sulfide / graphene composites, and nickel sulfide / carbon nanotube composites as electrode materials.

[0004] However, carbon-based materials are non-polar molecules with poor wettability in aqueous solutions and a hydrophobic surface, which is not conducive to their reaction in aqueous solutions, causing the reaction to remain only on the macroscopic surface of the material, resulting in uneven and incomplete reactions, and also not conducive to the contact and penetration of inorganic electrolytes. In addition, carbon-based materials have a large van der Waals attraction and tend to agglomerate with each other to form large blocks with a small specific surface area, which is not conducive to the exposure of catalytic hydrogenation active sites. Summary of the invention

[0005] The present invention provides a MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst, which has a core-shell structure formed by loosely arranging MS (M = Co and / or Ni) nanosheets with layered silicate disks as cores and wrapping them with shells, thereby overcoming the deficiencies of the above-mentioned prior art and effectively solving the problems of MS (M = Co and / or Ni) catalyst electrolyte penetration, small specific surface area, easy collapse of microstructure, and few active sites. The present invention creatively uses nano-sized layered silicate disks and cobalt sulfide or nickel shells to prepare MS (M = Co and / or Ni) / layered silicate nanocomposite catalysts, thereby achieving high-efficiency and long-life electrocatalytic water decomposition hydrogen production performance.

[0006] The invention discloses a MS (M=Co and / or Ni) / layered silicate nanocomposite catalyst, which comprises MS (M=Co and / or Ni) and a single layered silicate disc. The structure is a flower-like core-shell structure particle formed by a single layered silicate disc as a core and MS (M=Co and / or Ni) nanosheets loosely wrapped on the surface of the disc. The particle size of the MS (M=Co and / or Ni) / layered silicate nanocomposite catalyst is 80-200 nm; the shell thickness of the loosely arranged MS nanosheets is 60-180 nm; and the diameter of the layered silicate single-layer disc core is 1-45 nm.

[0007] The present invention provides a method for preparing a MS (M=Co and / or Ni) / layered silicate nanocomposite catalyst, which is obtained by the following steps:

[0008] (1) artificially synthesized layered silicate with a particle size of less than 100 nm and a disk diameter of less than 50 nm is dispersed in water, and a colorless transparent sol is formed under the action of at least one mechanical external force selected from high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring;

[0009] (2) at least one of nitrate, chloride, sulfate, oxalate, acetate, and citrate is used as a cobalt or nickel source, and at least one of soluble sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, thioacetamide, cysteine, and glutathione is dissolved in water as a sulfur source to form a MS (M = Co and / or Ni) precursor solution; the molar ratio of M / S in the precursor solution is 1:1 to 1:3.

[0010] (3) The silicate sol obtained in (1) and the MS (M = Co and / or Ni) precursor solution obtained in (2) are mixed under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring to form a uniform mixed sol; the mass ratio of layered silicate to MS (M = Co and / or Ni) in the mixed sol is between 0.1 and 1.

[0011] (4) The mixed sol obtained in (3) can be further crystallized at 120-220° C. for 3-72 hours, preferably 180-200° C. for 3-72 hours. The crystallization method can be a closed system oven, electric furnace heating crystallization, microwave heating crystallization, open system oil bath heating crystallization and other common crystallization methods; the product separation in the formed gel can be a polar solvent sedimentation separation, vacuum filtration separation and centrifugal separation. The product washing is washed with deionized water and ethanol to obtain MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst.

[0012] The MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst prepared by the present invention is used for the electrocatalytic decomposition of water to produce hydrogen. The electrochemical properties of the prepared samples were tested in a three-electrode system at room temperature, and the electrochemical workstation was CHI760E (Chenhua, Shanghai, China). The reaction conditions were: 0.5 M H 2 SO 4 In the system, Ag / AgCl electrode was used as reference electrode, carbon rod was used as counter electrode, 0.5×0.5cm 2 The MS (M = Co and / or Ni) / layered silicate was directly used as the working electrode.

[0013] The catalyst characterization results prepared by the present invention: The size of the CoS / layered silicate nanocomposite catalyst prepared by the present invention is about 180nm (see Figure 1 ), which are highly dispersed nano-flower-shaped particles with a specific surface area of ​​up to 126m 2 / g. The size of the NiS / layered silicate nanocomposite catalyst prepared by the present invention is about 120nm (see Figure 2 ), which are highly dispersed nano-flower-like particles with a specific surface area of ​​up to 153m 2 / g. The particle size of pure CoS catalyst is micron-sized flower ball particles with a specific surface area of ​​only 5.2m 2 / g(see Figure 1 The particle size of pure NiS catalyst is agglomerated micron-sized flower ball particles with a specific surface area of ​​only 8.9 m 2 / g(see Figure 2 ).

[0014] Compared with the prior art, the present invention has the following advantages and effects:

[0015] (1) The present invention prepares a MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst by compounding MS (M = Co and / or Ni) with a nano-sized layered silicate core-shell structure. The layered silicate disk is the core of the nanoparticle, has good hydrophilic swelling properties, and can increase the hydrophilicity of the electrode material. The loosely arranged shell layer of CoS and / or NiS nanosheets can promote the penetration of the electrolyte and the full contact with the electrode material, thereby avoiding the volume expansion effect on the microstructure of CoS and / or NiS and the collapse of the electrode structure, and improving the structural stability of the electrode material. The loosely arranged core-shell structure and the nanoparticle size of CoS and / or NiS have a high specific surface area, increase the exposure of active sites, and improve the electrocatalytic hydrogen production activity. In summary, the present invention solves the problems of the difficulty of the electrolyte solution to penetrate into the interior of the electrode material in the electrocatalytic decomposition of water to produce hydrogen, the small effective specific surface area of ​​the catalyst, and the low activity and poor stability of the catalytic material, and achieves high efficiency, long life, and high economic electrocatalytic hydrogen evolution performance.

[0016] (2) The MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst prepared by the present invention has a high specific surface area, a stable structure, and a large number of active sites; it has high activity and good stability when used for the electrocatalytic decomposition of water to produce hydrogen; the reaction results are detailed in Figure 3 and 4 The MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst of the present invention can have overpotentials as low as 90 mV / dec and 83 mV / dec in the electrocatalytic decomposition of water to produce hydrogen. -2 The overpotentials of the comparison samples CoS and NiS catalysts for electrocatalytic decomposition of water to produce hydrogen are 150mV / dec and 143mV / dec respectively. -2 The voltages are 0.376V and 0.363V respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 SEM photos of pure CoS obtained in Comparative Example 1 and CoS / layered silicate nanocomposite catalyst obtained in Example 3.

[0018] Figure 2 SEM photos of pure NiS obtained in Comparative Example 2 and NiS / layered silicate nanocomposite catalyst obtained in Example 6.

[0019] Figure 3 Electrocatalytic hydrogen production activity of pure CoS obtained in Comparative Example 1 and CoS / layered silicate nanocomposite catalyst obtained in Example 3.

[0020] Figure 4 Electrocatalytic hydrogen production activity of pure NiS obtained in Comparative Example 2 and NiS / layered silicate nanocomposite catalyst obtained in Example 6. DETAILED DESCRIPTION

[0021] In order to further illustrate the present invention, embodiments are given below, but they do not limit the scope of the present invention.

[0022] Embodiment 1:

[0023] Weigh 0.1g of magnesium silicate (magnesium lithium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 20nm, and a thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml of deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 3.1981g of cobalt nitrate hexahydrate and 3.3736g of glutathione and dissolve them in 60ml of water under stirring to form a CoS precursor solution. Mix the above-mentioned magnesium silicate sol and CoS precursor solution evenly for 10 minutes under 13000r.mp shear emulsification conditions to obtain a sol. The obtained sol is transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid. After freeze-drying for 12 hours, a CoS / magnesium silicate nanocomposite catalyst is obtained.

[0024] The test results of the nano-laser particle size analyzer show that the average particle size of the CoS / magnesium silicate composite catalyst obtained in this embodiment is 180nm, so CoS / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the CoS / magnesium silicate nano-composite catalyst obtained in this embodiment is a flower-shaped nanoparticle assembled from CoS nanosheets, and the particle size is 150-200nm. HRTEM characterization results show that the CoS / magnesium silicate nano-composite catalyst is a flower-shaped core-shell particle; the shell layer composed of loosely arranged CoS nanosheets is 80nm thick; the distance between the two farthest points on the side of the CoS nanosheet is 43nm, and the thickness is 4.3nm; the diameter of the layered silicate monolayer disk core is 15-25nm. The physical adsorption results show that the specific surface area of ​​the composite catalyst is 126m 2 / g.

[0025] The catalyst prepared in this example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of its hydrogen production reaction activity are shown in Table 1. The overpotential of the CoS / layered magnesium silicate nanocomposite catalyst of the present invention is much lower than that of the pure CoS catalyst.

[0026] Embodiment 2:

[0027] Weigh 0.5g of magnesium silicate (magnesium lithium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 20nm, and a thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml of deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 3.6146g of cobalt chloride and 1.6483g of thioacetamide and dissolve them in 60ml of water under stirring to form a CoS precursor solution. Under shear emulsification conditions, the above-mentioned magnesium silicate sol and CoS precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized in an oven at 180°C for 6 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid. After vacuum drying for 12 hours, a CoS / magnesium silicate nanocomposite catalyst is obtained.

[0028] The test results of the nano-laser particle size analyzer show that the average particle size of the CoS / magnesium silicate composite catalyst obtained in this embodiment is 150nm, so CoS / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the CoS / magnesium silicate nano-composite catalyst obtained in this embodiment is a flower-shaped nanoparticle assembled from CoS nanosheets, and the particle size is 120-170nm. HRTEM characterization results show that the CoS / magnesium silicate nano-composite catalyst is a flower-shaped core-shell particle; the distance between the two farthest points on the side of the CoS nanosheet is 38nm, and the thickness is 3.2nm; the shell layer composed of loosely arranged CoS nanosheets is 70nm thick; the diameter of the layered silicate monolayer disk core is 15-25nm. The physical adsorption results show that the specific surface area of ​​the composite catalyst is 147m 2 / g.

[0029] The catalyst prepared in this example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of its hydrogen production reaction activity are shown in Table 1. The overpotential of the CoS / layered magnesium silicate nanocomposite catalyst of the present invention is much lower than that of the pure CoS catalyst.

[0030] Embodiment 3:

[0031] Weigh 1.0g of magnesium silicate (magnesium lithium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 20nm, and a thickness of 1.0nm measured by a nano-laser particle size analyzer) and disperse it in 60ml of deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 2.7371g of cobalt acetate and 3.9890g of L-cysteine ​​and dissolve them in 60ml of water under stirring to form a CoS precursor solution. Under shear emulsification conditions, the above-mentioned magnesium silicate sol and CoS precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized at 180°C for 12 hours. After cooling to room temperature, it is filtered after sedimentation, washed with deionized water 3 times, and washed with ethanol 3 times to obtain a black solid. After drying naturally for 24 hours, a CoS / magnesium silicate nanocomposite catalyst is obtained.

[0032] The test results of the nano-laser particle size analyzer show that the average particle size of the CoS / magnesium silicate composite catalyst obtained in this embodiment is 120nm, so CoS / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the CoS / magnesium silicate nano-composite catalyst obtained in this embodiment is a flower-shaped nanoparticle assembled from CoS nanosheets, and the particle size is 100-150nm. HRTEM characterization results show that the CoS / magnesium silicate nano-composite catalyst is a flower-shaped core-shell particle; the distance between the two farthest points on the side of the CoS nanosheet is 22nm, and the thickness is 2.0nm; the shell layer composed of loosely arranged CoS nanosheets is 50nm thick; the diameter of the layered silicate monolayer disk core is 15-25nm. The physical adsorption results show that the specific surface area of ​​the composite catalyst is 188m 2 / g.

[0033] The catalyst prepared in this example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of its hydrogen production activity are shown in Table 1. The overpotential of the CoS / layered lithium magnesium silicate nanocomposite catalyst of the present invention is much lower than that of the pure CoS catalyst.

[0034] Embodiment 4:

[0035] Weigh 0.1g Lapointe (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, thickness 0.92nm) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 1.6121g nickel oxalate and 0.8352g thiourea and dissolve them in 60ml water under stirring to form a NiS precursor solution. Under shear emulsification conditions, the above Lapointe sol and NiS precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid. After vacuum drying for 24 hours, a NiS / Lapointe nanocomposite catalyst is obtained.

[0036] The test results of the nano-laser particle size analyzer show that the average particle size of the NiS / magnesium silicate composite catalyst obtained in this embodiment is 120nm, so NiS / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the NiS / magnesium silicate nano-composite catalyst obtained in this embodiment is a flower-shaped nanoparticle assembled from NiS nanosheets, and the particle size is 100-150nm. HRTEM characterization results show that the NiS / magnesium silicate nano-composite catalyst is a flower-shaped core-shell particle; the distance between the two farthest points on the side of the NiS nanosheet is 27nm, and the thickness is 2.4nm; the shell layer composed of loosely arranged NiS nanosheets is 50nm thick; the diameter of the layered silicate monolayer disk core is 20nm. Physical adsorption results show that the specific surface area of ​​the composite catalyst is 153m 2 / g.

[0037] The catalyst prepared in this example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of the hydrogen production reaction activity are shown in Table 1. The overpotential of the NiS / Lapointe nanocomposite catalyst of the present invention is much lower than that of the pure NiS catalyst.

[0038] Embodiment 5:

[0039] Weigh 0.5g sodium magnesium silicate (Shanghai Aladdin Biochemical Technology Co., Ltd., natural clay, average particle size 90nm, single-layer disc size 40nm, thickness 0.98nm) and disperse it in 60ml deionized water. Shear emulsify for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 4.0606g nickel citrate and 5.2747g sodium sulfide and dissolve them in 60ml water under stirring to form a NiS precursor solution. Under shear emulsification conditions, the above sodium magnesium silicate sol and NiS precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a hydrothermal kettle with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, direct suction filtration is performed, and deionized water is washed 3 times to obtain a black solid, which is vacuum dried for 24 hours to obtain a NiS / sodium magnesium silicate nanocomposite catalyst.

[0040] The test results of the nano-laser particle size analyzer show that the average particle size of the NiS / magnesium silicate composite catalyst obtained in this embodiment is 95nm, so NiS / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the NiS / magnesium silicate nano-composite catalyst obtained in this embodiment is a flower-shaped nanoparticle assembled from NiS nanosheets, and the particle size is 90-110nm. HRTEM characterization results show that the NiS / magnesium silicate nano-composite catalyst is a flower-shaped core-shell particle; the distance between the two farthest points on the side of the NiS nanosheet is 23nm, and the thickness is 2.1nm; the shell layer composed of loosely arranged NiS nanosheets is 47nm thick; the diameter of the layered silicate monolayer disk core is 20nm. The physical adsorption results show that the specific surface area of ​​the composite catalyst is 177m 2 / g.

[0041] The catalyst prepared in this example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of the hydrogen production reaction activity are shown in Table 1. The overpotential of the NiS / sodium magnesium silicate nanocomposite catalyst of the present invention is much lower than that of the pure NiS catalyst.

[0042] Embodiment 6:

[0043] Weigh 1.0g of lithium magnesium silicate (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single-layer disc size 25nm, thickness 1.0nm) and disperse it in 60ml of deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 3.0869g of nickel sulfate and 3.9890g of L-cysteine ​​and dissolve them in 60ml of water under stirring to form a CoS precursor solution. Under shear emulsification conditions, the above-mentioned lithium magnesium silicate sol and CoS precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a round-bottom flask with a reflux device and crystallized at 120°C in an oil bath for 60 hours. After cooling to room temperature, it is filtered after sedimentation and washed with deionized water 3 times to obtain a black solid. After freeze-drying for 6 hours, a NiS / lithium magnesium silicate nanocomposite catalyst is obtained.

[0044] The test results of the nano-laser particle size analyzer show that the average particle size of the NiS / magnesium silicate composite catalyst obtained in this embodiment is 80nm, so NiS / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the NiS / magnesium silicate nano-composite catalyst obtained in this embodiment is a flower-shaped nanoparticle assembled from NiS nanosheets, and the particle size is 70-90nm. HRTEM characterization results show that the NiS / magnesium silicate nano-composite catalyst is a flower-shaped core-shell particle; the distance between the two farthest points on the side of the NiS nanosheet is 16nm, and the thickness is 1.7nm; the shell layer composed of loosely arranged NiS nanosheets has a thickness of 38nm; the diameter of the layered silicate monolayer disk core is 20nm. The physical adsorption results show that the specific surface area of ​​the composite catalyst is 195m 2 / g.

[0045] The catalyst prepared in this example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of the hydrogen production reaction activity are shown in Table 1. The overpotential of the NiS / lithium magnesium silicate nanocomposite catalyst of the present invention is much lower than that of the pure NiS catalyst.

[0046] Comparative Example 1:

[0047] 3.1981g of cobalt nitrate and 3.3736g of glutathione were weighed and dissolved in 60ml of water under stirring to form a CoS precursor solution. The resulting solution was transferred into a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, the solid was separated by suction and washed with deionized water three times to obtain a black solid, which was freeze-dried for 12 hours to obtain a CoS catalyst.

[0048] SEM characterization shows that the NiS catalyst obtained in this example is agglomerated micron-sized particles with smooth surface, and the particle size is 1 to 5 μm. The physical adsorption results show that the specific surface area of ​​the catalyst obtained in this comparative example is 5.2 m 2 / g.

[0049] The CoS comparative catalyst prepared in this comparative example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of its hydrogen production reaction activity are shown in Table 1.

[0050] Comparative Example 2:

[0051] 3.0869 g of nickel sulfate and 3.9890 g of L-cysteine ​​were weighed and dissolved in 60 ml of water under stirring to form a CoS precursor solution. The resulting solution was transferred into a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized in an electric furnace at 200°C for 24 hours. After cooling to room temperature, the solid was separated by suction filtration and washed with deionized water three times to obtain a black solid, which was freeze-dried for 12 hours to obtain a NiS catalyst.

[0052] SEM characterization shows that the NiS catalyst obtained in this example is a micron-sized particle formed by the aggregation of nanoparticles, with a particle size of 2 to 4 μm. The physical adsorption results show that the specific surface area of ​​the catalyst obtained in this comparative example is 8.9 m 2 / g.

[0053] The NiS comparative catalyst prepared in this comparative example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of its hydrogen production reaction activity are shown in Table 1.

[0054] Comparative Example 3:

[0055] Weigh 0.1g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium lithium silicate, average particle size 60nm, single layer disc size 25nm, single layer disc thickness 0.92nm) and disperse it in 60ml deionized water. Stir magnetically for 1 hour to form a colorless transparent sol. Dissolve 2.0016g ferric nitrate nonahydrate and 1.875g thiourea in water to form FeS x Precursor solution. Laponite sol and FeS x The precursor solution was mixed with magnetic stirring for 1 hour to form a uniform mixed sol. The obtained sol was transferred to a three-necked flask and refluxed in an oil bath at 140°C for crystallization for 48 hours. After cooling to room temperature, it was separated by suction filtration and washed with deionized water 3 times to obtain a black solid, which was directly dispersed in decahydronaphthalene to obtain FeS x / Laponite nanocomposite catalyst slurry.

[0056] The test results of the nano-laser particle size analyzer show that the FeS x The average particle size of the FeS / Laponite composite catalyst is 40 nm. x / Laponite is a nanocomposite catalyst. SEM characterization shows that the FeS x / Laponite nanocomposite catalyst is loose nanoparticles with a particle size of 38-40 nm; HRTEM characterization results show that FeS x Spherical nanoparticles are composited with a single layered Laponite disk. The spherical FeS x The diameter of the nanoparticles is 4-5nm, without agglomeration; the diameter of the single layered Laponite disk is 25nm. The physical adsorption results show that the specific surface area of ​​the composite catalyst is 164m 2 / g.

[0057] The comparative catalyst prepared in this comparative example was used for the electrocatalytic decomposition of water to produce hydrogen. The results of its hydrogen production reaction activity are shown in Table 1.

[0058] Table 1 Electrocatalytic hydrogen production activity of the MS (M = Co and / or Ni) / layered silicate nanocomposite catalyst prepared by the present invention and the control sample pure MS (M = Co and / or Ni) catalyst. Reaction conditions: 0.5 M H 2 SO 4 In the system, Ag / AgCl electrode was used as reference electrode, carbon rod was used as counter electrode, 0.5×0.5cm 2 The MS (M = Co and / or Ni) / layered silicate was directly used as the working electrode. The preparation process of the working electrode was as follows: 5 mg of the catalyst was dispersed in 100 μl of ethanol, ultrasonically dispersed for 30 minutes, and 5 μl of the solution was dropped onto a 0.5×0.5 cm 2 After the solution dries, 2 μl of 0.3% Nafion ethanol solution is dropped onto the surface of the glassy carbon electrode and dried fully to obtain a working electrode.

[0059]

Claims

1. A MS / layered silicate nanocomposite catalyst, characterized in that: The MS / layered silicate nanocomposite catalyst comprises MS and a single layered silicate disk, and structurally, a single layered silicate disk is used as a core, and MS nanosheets are wrapped around the disk surface to form nanosheet-assembled core-shell structure particles or nanosheet-stacked flower-shaped core-shell structure particles; Wherein M in MS = Co and / or Ni; The distance between the two farthest points on the surface of the MS nanosheet is 15~50 nm, and the thickness is 0.5~6 nm; the thickness of the shell composed of the MS nanosheets is 30~90 nm; The preparation method of the catalyst comprises the following steps: (1) Dispersing layered silicate in water to form a colorless and transparent sol under the action of mechanical external force; (2) dissolving one or a mixture of two or more of nitrate, chloride, sulfate, oxalate, acetate, and citrate of cobalt and / or nickel as a cobalt source and / or a nickel source and a sulfur source in water to form a MS precursor solution; (3) mixing the silicate sol obtained in step (1) and the MS precursor solution obtained in step (2) under the action of an external mechanical force to form a uniform mixed sol; (4) subjecting the mixed sol obtained in step (3) to heat treatment, crystallization and cooling, and separating the product in the formed gel to obtain the MS / layered silicate nanocomposite catalyst; The layered silicate used is a chemically synthesized layered silicate with a particle diameter of 10-100 nm and a single-layer disk diameter of 1-50 nm, and is one or more of magnesium silicate, lithium magnesium silicate, and sodium magnesium lithium silicate; the thickness of the single-layer disk is 0.4-1.8 nm; The sulfur source is one or a mixture of two or more of soluble sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, thioacetamide, cysteine ​​and glutathione.

2. The catalyst according to claim 1, characterized in that: The mass ratio of layered silicate to MS in the MS / layered silicate nanocomposite catalyst is 0.1-1.0; the catalyst particle size is 80-200 nm; The diameter of the layered silicate single-layer disk core is 1-45 nm.

3. The catalyst according to claim 1, characterized in that: The molar ratio of M to S in the mixed sol is 1:1~1:3; the mass ratio of layered silicate to MS in the mixed sol is 0.1~1.

0.

4. The catalyst according to claim 1, characterized in that: The mechanical external force used to form the sol includes one or more of high-speed shear emulsification, mechanical stirring, magnetic stirring, manual stirring and ultrasound.

5. The catalyst according to claim 1, characterized in that: The mass concentration range of the layered silicate in the mixed sol in step (3) is 0.5-40 mg / mL; the synthesis system in the crystallization heat treatment process in step (4) is in a gel state; the crystallization temperature of the mixed sol is 120-220° C. and the crystallization time is 3-72 hours.

6. The catalyst according to claim 5, characterized in that: The crystallization temperature of step (4) is 180-200°C.

7. Use of the MS / layered silicate nanocomposite catalyst according to claim 1 in the electrocatalytic decomposition of water to produce hydrogen.

Citation Information

Patent Citations

  • Preparation method of nickel sulfide-graphene nano composite material

    CN105206816A

  • Cobalt-nickel sulfide / nitrogen-doped carbon nano-fiber composite material, preparation method and application thereof

    CN106298269A

  • A nickel disulfide-carbon composite material, its preparation method and application

    CN108390044B

  • Application of nickel sulfide / carbon nanotube flexible composite thin film material on supercapacitor

    CN109872881A

  • Nickel sulfide / carbon nano tube flexible composite thin-film material and preparation method and application thereof

    CN109873127A